Pengaruh Fitur, Kualitas Produk dan Bagi Hasil terhadap Loyalitas Nasabah Tabungan Mudharabah di Bank Syariah Mandiri Kantor Cabang Pembantu Rancaekek - Nur'aeni Nur'aeni; Susi Susanti; Mimin Mintarsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Currently, Islamic banks are required to continue to make improvements in order to increase customer satisfaction and ultimately make them loyal to the products offered. Especially the Mudaraba savings which are the prima donna products of Islamic banking. This study seeks to find the effect of features, product quality, and profit-sharing on the loyalty of Mudaraba savings customers. This research was conducted on customers at Bank Syariah Mandiri Branch Office Rancaekek with the number of respondents as many as 82 people. Data analysis using multiple linear regressions. The results of the study reveal that features, product quality, and profit-sharing have a significant effect on customer loyalty in Mudaraba savings.